Implementation of a Holistic Approach in Preconception Programs to Improve Reproductive Health in Young Couples in Bungursari District - Purnamawati, Leli; Amanah , Siti (Jurnal Indonesia Sosial Sains, 2025)
Reproductive health is an important aspect of preparing for a healthy pregnancy. Preconception programs aim to improve the physical, mental, social, and environmental readiness of couples before pregnancy. This study aims to analyze the implementation of a holistic approach in preconception programs to improve the reproductive health of young couples in Bungursari District. The research method used a quantitative descriptive design with a cross-sectional approach, involving 100 couples of childbearing age who participated in a preconception program at the Bungursari Health Center. Data were collected through questionnaires, in-depth interviews, and observations. The results of the study showed that a holistic approach that includes nutrition education, psychological counseling, health checks, and increased social support was able to increase the score of reproductive health knowledge, attitudes, and practices by 35%. In conclusion, the application of a holistic approach is effective in increasing the preconception readiness of young couples. It is recommended that this program be implemented in a sustainable manner throughout the region.